2022
DOI: 10.1002/ece3.9169
|View full text |Cite
|
Sign up to set email alerts
|

Past, present, and future predictions on the suitable habitat of the Slender racer (Orientocoluber spinalis) using species distribution models

Abstract: Species distribution models (SDMs) across past, present, and future timelines provide insights into the current distribution of these species and their reaction to climate change. Specifically, if a species is threatened or not well‐known, the information may be critical to understand that species. In this study, we computed SDMs for Orientocoluber spinalis , a monotypic snake genus found in central and northeast Asia, across the past (last interglacial, last glacial maximum, and mid‐Hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 133 publications
(159 reference statements)
0
11
0
Order By: Relevance
“…Cautions are need for the growing amount of herpetofauna import 43 through the coasts. Since many studies revealed that herpetofauna of the Korean Peninsula are especially susceptible to climate change 28,[44][45][46] , the southern ecosystems need a particular conservation concern as habitats there will be disappeared sooner than later [45][46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…Cautions are need for the growing amount of herpetofauna import 43 through the coasts. Since many studies revealed that herpetofauna of the Korean Peninsula are especially susceptible to climate change 28,[44][45][46] , the southern ecosystems need a particular conservation concern as habitats there will be disappeared sooner than later [45][46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…Species distribution models (SDMs) are important for analyzing the spatial and temporal processes that make up a species’ life cycle. Additionally, SDMs for historical timelines can also offer ecological and evolutionary data on the historical changes of species distribution over time ( Park et al., 2022 ). Past models can be used to explain phylogeographic patterns and speciation processes, as well as to predict historical hotspots and potential migration routes ( Park et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, SDMs for historical timelines can also offer ecological and evolutionary data on the historical changes of species distribution over time ( Park et al., 2022 ). Past models can be used to explain phylogeographic patterns and speciation processes, as well as to predict historical hotspots and potential migration routes ( Park et al., 2022 ). Additionally, studies on how species have adapted to past climate change offer important insights into how species will respond to climate change in the future ( Pearson, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…This method proved effective and economical for gathering species occurrences where scientifically designed surveys would require time‐consuming field efforts (Johnson et al, 2020), with successful applications also on invasive alien species (Grez et al, 2022; Maistrello et al, 2016; Werenkraut et al, 2020). In recent years, citizen science initiatives have increasingly been used by researchers as a source of occurrence data to model the distribution of species in both native (Arenas‐Castro et al, 2022; Milanesi et al, 2020; Park et al, 2022; Stuber et al, 2022) and invaded ranges (Di Febbraro et al, 2019; Giuntini et al, 2022; Tran et al, 2022). The availability of abundant and widely distributed occurrence records represented a key characteristic behind the growing importance of citizen science initiatives in modelling studies, especially as providers of presence‐only data (Fletcher et al, 2019; Johnston et al, 2022).…”
Section: Introductionmentioning
confidence: 99%